2019
DOI: 10.15185/izawol.111.v2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation and labor market outcomes

Abstract: Despite anti-discrimination laws in some countries, gay and lesbian employees encounter serious job market barriers. They report more harassment and less job satisfaction than heterosexual employees, and gay men earn less than comparably skilled and experienced heterosexual men. Good employer-employee relations are shown to increase job satisfaction for gay and lesbian employees. Government can help through campaigns promoting respect and equality of treatment in the workplace and by publishing annual data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
112
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(115 citation statements)
references
References 6 publications
1
112
0
2
Order By: Relevance
“…Support is very important for LGBT employees due to the unique stressors they experience (Huffman et al, ). It is expected that the existence of an LGBT group in the workplace could improve the visibility and experiences of its members by establishing anti‐discrimination and anti‐bullying policies and procedures (Huffman et al, ; Drydakis, ). On the basis of these patterns, we formulate the following as the fourth hypothesis related to the existence of an LGBT group in the workplace and workplace bullying:
Hypothesis 4.
…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Support is very important for LGBT employees due to the unique stressors they experience (Huffman et al, ). It is expected that the existence of an LGBT group in the workplace could improve the visibility and experiences of its members by establishing anti‐discrimination and anti‐bullying policies and procedures (Huffman et al, ; Drydakis, ). On the basis of these patterns, we formulate the following as the fourth hypothesis related to the existence of an LGBT group in the workplace and workplace bullying:
Hypothesis 4.
…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, openness about one’s sexual orientation in the workplace has been found to positively affect job satisfaction (Huffman et al, ; Drydakis, ). We suggest that firms that have LGBT groups might foster openness (Drydakis, ). On the basis of the patterns presented, we formulate the following as the seventh hypothesis, related to the existence of an LGBT group in the workplace and job satisfaction:
Hypothesis 7.
…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed et al. , ; Carpenter ; Drydakis ; Elmslie and Tebaldi ; Klawitter ; Martell ), but lesbians earn more than their heterosexual counterparts (e.g. Ahmed et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some research also showed that there is a substantial pay gap between gay and lesbian workers and their heterosexual counterparts even in countries such as Canada, Sweden, Australia, and the Netherlands with established gay rights legislation (Drydakis ). The size of these estimates, however, varies widely, and some even found there are no differences in earnings between LG persons and their heterosexual counterparts (e.g.…”
Section: Introductionmentioning
confidence: 99%